Characterization of the lipidome profile from two brown macroalgae, Sargassum muticum and Bifurcaria bifurcata and their bioactive properties - Santos, Fábio da Fonte (2019)
Brown macroalgae elicited great interest due to their nutritional properties and biochemical composition rich in compounds with bioactive properties that can be used in pharmaceutical, nutritional and cosmetical applications. Among the lipids in algae, polar lipids such phospholipids and glycolipids have been associated to anti-inflammatory and antioxidant properties that have triggered the interest of the scientific community. However, the polar lipid composition of brown macrolagae is poorly known. Therefore, this work intended to identify the polar lipid composition of brown macroalgae Sargassum muticum and Bifurcaria bifurcata from the Portuguese coast, and to evaluate their antioxidant properties. The characterization of the polar lipid profile was performed using mass spectrometry coupled with liquid chromatography, HILICESI-MS and MS/MS. The fatty acid profile of these polar lipids was determined by CG-MS. The polar lipid profile of Sargassum muticum and Bifurcaria bifurcata revealed the presence of 176 and 141different molecular lipid species respectively, distributed between glycolipids, phospholipids and betaine lipids. Some of the identified lipid species were previously associated with bioactive properties. Fatty acid profile present in these lipid classes includes polyunsaturated fatty acids (PUFA), namely 18:3 n-3, 18:4 n-3, 20:4 n-6 and 20:5 n-3 that have nutritional value. Both lipidic extracts revealed antioxidant activity, but with better results in the case of S. muticum highlighting best antioxidant results. In a general way, the results obtained showed that both lipid extracts can be promising for pharmaceutical, biomedical and nutritional applications, contributing to the valorisation of these two macroalgae as a source of bioactive and added-value compounds.